2012
DOI: 10.1105/tpc.112.105106
|View full text |Cite
|
Sign up to set email alerts
|

A Galactoglycerolipid Lipase Is Required for Triacylglycerol Accumulation and Survival Following Nitrogen Deprivation in Chlamydomonas reinhardtii

Abstract: Following N deprivation, microalgae accumulate triacylglycerols (TAGs). To gain mechanistic insights into this phenomenon, we identified mutants with reduced TAG content following N deprivation in the model alga Chlamydomonas reinhardtii. In one of the mutants, the disruption of a galactoglycerolipid lipase-encoding gene, designated PLASTID GALACTOGLYCEROLIPID DEGRADATION1 (PGD1), was responsible for the primary phenotype: reduced TAG content, altered TAG composition, and reduced galactoglycerolipid turnover. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
294
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(330 citation statements)
references
References 67 publications
(77 reference statements)
27
294
1
Order By: Relevance
“…It may be that the moderate light levels at which C. reinhardtii is cultured and at which NPQ was measured here are too low to induce significant quenching. Also, we observed little or no increase in the levels of ROS-related proteins (with the exception of modest increases in GPX5), which is consistent with a recent study in which no increases in ROS levels were detected during N deprivation in wild type C. reinhardtii (Li et al, 2012). Chl levels per cell decrease strongly, and this, together with changes in photosynthetic light use efficiency, can be estimated to reduce energy capture by approximately 3-fold within 24 h, consistent with the observation of strong reduction in the light-driven oxygen production rate.…”
Section: Photosynthesis Is Down-regulated In a Controlled And Orderlysupporting
confidence: 92%
See 2 more Smart Citations
“…It may be that the moderate light levels at which C. reinhardtii is cultured and at which NPQ was measured here are too low to induce significant quenching. Also, we observed little or no increase in the levels of ROS-related proteins (with the exception of modest increases in GPX5), which is consistent with a recent study in which no increases in ROS levels were detected during N deprivation in wild type C. reinhardtii (Li et al, 2012). Chl levels per cell decrease strongly, and this, together with changes in photosynthetic light use efficiency, can be estimated to reduce energy capture by approximately 3-fold within 24 h, consistent with the observation of strong reduction in the light-driven oxygen production rate.…”
Section: Photosynthesis Is Down-regulated In a Controlled And Orderlysupporting
confidence: 92%
“…During N deprivation, it has been suggested that photosynthesis induces significant stress via energetic overflows, leading to potential oxidative damage and driving starch and oil accumulation as energy sinks (Roessler, 1990;Hu et al, 2008;Li et al, 2012). Consistent with this, GPX5, a gene associated with reactive oxygen species (ROS), was up-regulated.…”
Section: Photosynthesis Is Down-regulated In a Controlled And Orderlymentioning
confidence: 82%
See 1 more Smart Citation
“…Increases in TAG inversely track with the decline in C20:5 FA concentrations in both cell types (Supplemental Figures 7C and 7D). In P. tricornutum and other microalgae, the decrease in C20:5 FA during N-stress is believed to reflect the efforts by alga to pursue a second source for TAG by recycling C20:5 and C16 FA moieties from chloroplast thylakoid membrane glycerolipids (Abida et al, 2015;Li et al, 2012;Martin et al, 2014;Simionato et al, 2013). Specific galactoglycerolipid lipases, known in plants as patatin lipases (reviewed in Scherer et al, 2010), have been functionally characterized in C. reinhardtii and Nannochloropsis oceanica Li et al, 2014) as thylakoid glycerolipid recyclers.…”
Section: Nitrate-replete Conditions Trigger Biosynthesis Of Lipids Inmentioning
confidence: 99%
“…Previous studies have assessed the responses of metabolic genes and proteins under non-steady state conditions when TAG accumulates (Miller et al, 2010;Boyle et al, 2012;Msanne et al, 2012;Blaby et al, 2013;Wase et al, 2014) or identified mutants that are defective for TAG accumulation or catabolism (Li et al, 2012;Boyle et al, 2012;Tsai et al, 2014;Xie et al, 2014;Ngan et al, 2015;Kajikawa et al, 2015). The relationship between starch synthesis and TAGs has also been investigated, and it appears that fixed carbon can be shunted toward TAGs when starch synthesis is blocked (Li et al, 2010a(Li et al, , 2010bWork et al, 2010;Siaut et al, 2011;Goodenough et al, 2014).…”
Section: Insps As a Metabolic Signal For Carbon Metabolismmentioning
confidence: 99%